Analisis Kebijakan Merger BSI Terhadap Industri Halal UMKM - Munandar, Arif; Arsa, Arsa; Subhan, Muhammad (STAI Denpasar Bali, 2023)
This study examines the Indonesian Islamic Bank Merger policy towards the halal industry for micro, small and medium enterprises. This research is to find out the role of the Indonesian Islamic Bank Jambi Gatot Subroto branch office in developing the halal industry Micro, small and medium enterprises that apply for financing at the Bank after the Merger and find out what are the obstacles faced by the Indonesian Islamic Bank Jambi Gatot Subroto branch office in distributing financing contracts to Micro, small and medium enterprises after the merger. This study uses a qualitative approach and the type of research approach used is descriptive qualitative. The data sources are primary data and secondary data. Methods of data collection through interviews and documentation. The results of this study indicate that the Indonesian Islamic Bank Jambi Gatot Subroto after the merger already has a role in improving the economy and developing the halal industry Micro, small and medium enterprises in Jambi City by providing an initial injection of funds and top up or additional business capital and also lightening and facilitating Micro, small and medium enterprises in applying for financing at Bank Syariah Indonesia, not only that, Bank Syariah Indonesia also plays an active role as a consultant for its customers and often holds entrepreneurship guidance, Bank Syariah Indonesia, the Jambi branch office, Gatot Subroto, conducts canvassing every day or goes directly into the field to spread brochures as well as reducing installments when customers are affected by natural disasters. The constraints of Bank Syariah Indonesia Gatot Subroto Jambi branch office in channeling financing to the Halal Industry Micro, small and medium enterprises, namely defects in the name of the customer concerned due to late payment of bills, problems when completing administrative requirements files because if one of the requirements is not completed then the financing cannot be continued , business constraints that are already running but the customer is dishonest regarding customer financial information, accounts payable or reports about business activities that the customer is running, and constraints from the bank itself, namely when the customer data input system has an error while doing financing.